Kolbe-Schmitt screening reaction conditions using supercritical carbon dioxide - Young, Mei Yao (2022)
Salicylic acid derivatives from phenols with CO2 are synthesised in the industry by a base-promoted Kolbe–Schmitt carboxylation reaction, however the mechanism is still unclear. Numerous studies and investigations were conducted on finding methods to improve the reaction conditions of the Kolbe – Schmitt reaction as well as increasing the product yield. This thesis is centred on the Kolbe – Schmitt screening reaction conditions using supercritical CO2 for the synthesis of over-based detergents. The synthesis of sodium alkyl salicylate from sodium alkyl phenolate and CO2 under several parameters ranging from reaction time, high temperatures, the use of promoters and two CO2 pressure – supercritical and gaseous. The promising parameters were then applied to the synthesis of calcium alkyl salicylate from calcium alkyl phenolate and CO2. The overall aim is to synthesise calcium alkyl salicylate directly by Kolbe – Schmitt reaction by using the optimal parameters used in synthesising sodium alkyl salicylate.